Pentingnya Pengetahuan Gizi pada Ibu Hamil Terhadap Kesehatan Ibu dan Anak - Imani, Siti Nur; Kurniasari, Ratih (JGK: Jurnal Gizi dan Kesehatan, 2022)
Background:The development of a nation is essentially to realize the welfare of the people. Efforts to improve the quality of human resources should start as early as possible since the fetus is in the womb. Pregnant women are one of the most vulnerable groups to nutritional problems. Purpose:The purpose of counseling can minimize the occurrence of malnutrition in the community and pregnant women can know the importance of good nutrition for children. Method of literature study or library research. This literature study was carried out by reading relevant sources to obtain the necessary data. Nutritional problems experienced by pregnant women before or during pregnancy can affect the growth of the fetus that is being conceived. Malnourishment can trigger stunting due to prolonged malnutrition in the first 1,000 days of life (HPK). Indonesia is currently having a problem with stunting. The level of one's nutritional knowledge will affect attitudes and behavior in food selection. Results: This study shows that, after testing the effect of knowledge scores on the knowledge of the intervention group and the control group, it is found that there is a significant effect between the knowledge scores. Conclusion: From the results of this research activity it is necessary to have education about balanced nutrition to be able to increase the knowledge of pregnant women.